Super Vertex Magic Circulant Graphs - Liu, Chih-Hsiuan; Chia, Ming-I; Zhang, Guang-Hui; Wang, Tao-Ming (Utilitas Mathematica, 2019)
Let G = (V, E) be a finite simple graph with p = |V| vertices and q=\E\ edges, without any isolated vertex or any isolated edge. A vertex magic total labeling of the graph G is a bijection/from V U E to the set of consecutive integers (1,2, • •• }p + q}> such that for every vertex u e V, the weight f(u) + Y^uvtE f(uv) constant. Moreover if/(V) = {1,2, • • •, p},/is called a super vertex magic total labeling. A graph is (super) vertex magic if it admits a (super) vertex magic total labeling. In 2002 MacDougall et al. first introduced the concept of vertex magic total labeling and studied. © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.